Energy harvesting from a novel contact-type dielectric elastomer generator. (1st February 2020) - Zhang, C.L.; Lai, Z.H.; Rao, X.X.; Zhang, J.W.; Yurchenko, D.
Highlights: A novel dielectric elastomer generator is proposed to harvest contact-type energy. Energy can be harvested from two dielectric elastomer membranes in turn. The energy harvesting behavior is verified experimentally. System performance is decided by the amplitude and period of excitations. Structure parameters, pre-stretched ratio and input voltage affect EH performance. Abstract: A novel contact-type (CT) dielectric elastomer generator (DEG), which can harvest energy from two dielectric elastomer membranes (DEMs) under a regular contact-type displacement excitation, is proposed and studied in this paper. The operating principle of the proposed CT DEG is introduced with its electrical outputs under a contact being derived. This is further verified by capacitance and output voltage measurement experiments, thus making the theoretical analysis credible. Furthermore, the energy harvesting (EH) performance of the CT DEG in simulated contact environments is fully investigated through the conducted numerical simulations, and the influences of the excitation parameters, the system structure parameters, the pre-stretched ratio of DEM and input voltage are studied. It was found that the system demonstrates a better EH performance under a larger amplitude and a smaller period of the excitation, and the system EH performance can be enhanced by increasing the plate's radius, the pre-stretched ratio, the input voltage or decreasing the DEM's radius. By adjusting these parameters appropriately, the system output voltage can be 10 times higher than the input voltage, and the system output power can be achieved as high as 22.94 mW under a given displacement excitation. The research results can provide some effective solutions for the design and improvement of the proposed CT DEG in contact-type energy harvesting.